2002
DOI: 10.1088/0953-2048/15/6/321
|View full text |Cite
|
Sign up to set email alerts
|

Polycrystalline (Tl0.5Pb0.5)(Sr0.9Ba0.1)2Ca2Cu3Oy superconducting thick films with high critical current densities

Abstract: Superconducting (Tl 0.5 Pb 0.5 )(Sr 0.9 Ba 0.1 ) 2 Ca 2 Cu 3 O y films were fabricated on lanthanum aluminate substrates by screen printing of the precursor material followed by ex situ thallination. The thickness of the films varied between 1.3 and 2.6 µm. X-ray diffraction and optical microscopy showed that the films were highly textured. Samples with critical temperatures T c(0) between 116 and 120 K and with transition widths T (90−10%) of 1 K have been fabricated. Critical current densities between 0.6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Unique properties of superconducting devices like an extremely small energy consumption and a picosecond range switching speed force to develop so-called superconductor digital (737) electronics which can also use thallium base HTS [2]. The wide researches on lead doped thallium superconductors (Tl-1223) showed that critical current densities of more than 10 6 A/cm 2 may be achieved for Tl-1223 films on single-crystalline lanthanum aluminate as substrate [3][4][5][6]. Current investigation showed that c-axis oriented Tl-1223 films may also be prepared on silver [7,8] by a two-step preparation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Unique properties of superconducting devices like an extremely small energy consumption and a picosecond range switching speed force to develop so-called superconductor digital (737) electronics which can also use thallium base HTS [2]. The wide researches on lead doped thallium superconductors (Tl-1223) showed that critical current densities of more than 10 6 A/cm 2 may be achieved for Tl-1223 films on single-crystalline lanthanum aluminate as substrate [3][4][5][6]. Current investigation showed that c-axis oriented Tl-1223 films may also be prepared on silver [7,8] by a two-step preparation technique.…”
Section: Introductionmentioning
confidence: 99%
“…The film was prepared using screen printing method and the details of preparation and structural analysis are described in the papers [2,9]. The X-ray diffraction showed the high purity of the sample and tetragonal structure.…”
Section: Resultsmentioning
confidence: 99%
“…Samples 1 and 2 were prepared by screen printing thallium-free precursor material on monocrystalline (100) lanthanum aluminate substrates followed by ex situ thallination. The preparing procedures are described in earlier papers [1,2,5,6]. The resulting films were quasi-monocrystalline with high ab alignment and c-axis orientation and of high purity.…”
Section: Methodsmentioning
confidence: 99%
“…Within last years considerable progress in improving electrical transport properties in such films was made. High-purity, well aligned Tl-1223 based superconducting films with critical current densities close to 10 6 A cm −2 were already produced [1,2]. Superconducting films are very convenient for application of the electric transport methods in the critical current investigations due to their small cross-section -they do not need large currents for such measurements.…”
Section: Introductionmentioning
confidence: 99%